2019
DOI: 10.1093/gbe/evz032
|View full text |Cite
|
Sign up to set email alerts
|

Multifarious Evolutionary Pathways of a Nuclear RNA Editing Factor: Disjunctions in Coevolution of DOT4 and Its Chloroplast Target rpoC1eU488SL

Abstract: Nuclear-encoded pentatricopeptide repeat (PPR) proteins are site-specific factors for C-to-U RNA editing in plant organelles coevolving with their targets. Losing an editing target by C-to-T conversion allows for eventual loss of its editing factor, as recently confirmed for editing factors CLB19, CRR28, and RARE1 targeting ancient chloroplast editing sites in flowering plants. Here, we report on alternative evolutionary pathways for DOT4 addressing rpoC1eU488SL, a chloroplast editing site in the RNA polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 80 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Comparing plant lifestyles gives no reasonable clues as to why some plant lineages (like the Selaginellales) have lost reverse RNA editing altogether, may have never possessed it in the first place (possibly mosses and liverworts, depending on the ultimately true phylogeny of the bryophyte clades), or why U-to-C editing may even dominate over C-to-U editing in other lineages . Based on the working hypotheses presented here, the experimental approaches outlined herein will hopefully help to answer that puzzling evolutionary question or, for example, also why RNA editing evolves so dramatically fast in at least some genera, like Amaranthus or Silene among the angiosperms (Sloan et al, 2010;Hein et al, 2019), Selaginella among the lycophytes (Smith, 2019), Adiantum among ferns (Zumkeller et al, 2016), or, as also demonstrated here for U-to-C editing, in Anthoceros among the hornworts.…”
Section: New Phytologistmentioning
confidence: 75%
“…Comparing plant lifestyles gives no reasonable clues as to why some plant lineages (like the Selaginellales) have lost reverse RNA editing altogether, may have never possessed it in the first place (possibly mosses and liverworts, depending on the ultimately true phylogeny of the bryophyte clades), or why U-to-C editing may even dominate over C-to-U editing in other lineages . Based on the working hypotheses presented here, the experimental approaches outlined herein will hopefully help to answer that puzzling evolutionary question or, for example, also why RNA editing evolves so dramatically fast in at least some genera, like Amaranthus or Silene among the angiosperms (Sloan et al, 2010;Hein et al, 2019), Selaginella among the lycophytes (Smith, 2019), Adiantum among ferns (Zumkeller et al, 2016), or, as also demonstrated here for U-to-C editing, in Anthoceros among the hornworts.…”
Section: New Phytologistmentioning
confidence: 75%
“…Moreover, as revealed for DOT4 PPR protein -the loss of editing target site through C to T conversion allowed DOT4 in Poaceae to adapt for new function. Also some cases were described where the target sequences for editing exist, but no corresponding PPR is encoded by nucleus (Hein et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Here, four PPR genes, including PPRDOT4 (LOC104586410), PPRAt1g56570 (LOC104607063), PPRat2g04860 (LOC104609601), and PPRAt1g69350 (LOC104598024), were significantly down-regulated, and the expression levels of their regulator miRNAs, miR156_2 , miR157d-3p , and miR6300 , increased, respectively ( Tables S3–S5 ). Among them, PPRDOT4 mediated chloroplast RNA editing [ 78 ]. It has been reported that RF-PPR592, which belongs to the PPR protein family, can restore the fertility of cytoplasmic male sterile plants [ 79 ].…”
Section: Discussionmentioning
confidence: 99%